2017
DOI: 10.1097/ccm.0000000000002233
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Regional Differences of Local Pressure-Volume Curves With Electrical Impedance Tomography

Abstract: Electrical impedance tomography-derived maps of pressure-volume curve shapes allow to detect regions in which elastance changes during inflation. This could promote individualized mechanical ventilation by minimizing the probability of local tidal recruitment and/or overdistension. Electrical impedance tomography-derived maps might become clinically feasible and relevant, being simpler than currently available alternative approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…The previous studies also showed that reginal P-I curves in the dependent lung region were different from global and non-dependent lung region P-I curves, which had higher values of a lower inflection point indicating that higher pressure was needed to open atelectatic alveoli. 12 , 13 , 18 , 29 32 In our study, considering the optimization of ΔV DER-PI distribution between the two distinct regions, 10 cmH 2 O may represent the optimal PEEP level to maximize open alveoli and minimize alveoli overdistension. Although the regional P-I curves could provide more detailed information, the best way to determine the optimal PEEP levels based on regional recruitment volume was to balance overdistention and collapse, but this requires further investigation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The previous studies also showed that reginal P-I curves in the dependent lung region were different from global and non-dependent lung region P-I curves, which had higher values of a lower inflection point indicating that higher pressure was needed to open atelectatic alveoli. 12 , 13 , 18 , 29 32 In our study, considering the optimization of ΔV DER-PI distribution between the two distinct regions, 10 cmH 2 O may represent the optimal PEEP level to maximize open alveoli and minimize alveoli overdistension. Although the regional P-I curves could provide more detailed information, the best way to determine the optimal PEEP levels based on regional recruitment volume was to balance overdistention and collapse, but this requires further investigation.…”
Section: Discussionmentioning
confidence: 96%
“… 10 It is feasible to evaluate regional derecruitment with the regional P-I curves, as described in previous studies. 12 , 13 , 18 , 29 32 In this study, we calculated ΔV DER-PI that was induced by adjacent PEEP in nondependent and dependent lung regions by the regional P-I curves. The results have shown that the different lung regions have different responses to PEEP.…”
Section: Discussionmentioning
confidence: 99%
“…EIT-derived maps of P-V curve shapes are an newly proposed approach for detection of tidal recruitment and overdistension that could possibly be used to guide mechanical ventilation in the future (Beda et al, 2017). A recently proposed recruitment function could also be applied to identify the recruited volume at a given airway pressure (Uzawa et al, 2015) but requires further validation in human patient data.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Beda et al [ 34 ] showed that EIT-derived pressure–volume (PV) curves could identify regions of presumed tidal recruitment and overdistension. Changes in PV shape-derived tidal recruitment were correlated with changes in poorly aerated regions, and changes in PV shape-derived overdistension were highly correlated with changes in hyperaerated regions for higher PEEPs ( r = 0.73).…”
Section: Clinical Toolsmentioning
confidence: 99%